“Our voices matter”: a before-after assessment of the effect of a community-participatory intervention to promote uptake of maternal and child health services in Kwale, Kenya - Vernon Mochache; Eunice Irungu; Hajara El-Busaidy; Marleen Temmerman; Peter Gichangi (BMC Health Services Research, 2018)
Abstract Background Community-participatory approaches are important for effective maternal and child health interventions. A community-participatory intervention (the Dialogue Model) was implemented in Kwale County, Kenya to enhance uptake of select maternal and child health services among women of reproductive age. Methods Community volunteers were trained to facilitate Dialogue Model sessions in community units associated with intervention health facilities in Matuga, Kwale. Selection of intervention facilities was purposive based on those that had an active community unit in existence. For each facility, uptake of family planning, antenatal care and facility-based delivery as reported in the District Health Information System (DHIS)-2 was compared pre- (October 2012 – September 2013) versus post- (January – December 2016) intervention implementation using a paired sample t-test. Results Between October 2013 and December 2015, a total of 570 Dialogue Model sessions were held in 12 community units associated with 10 intervention facilities. The median [interquartile range (IQR)] number of sessions per month per facility was 2 (1–3). Overall, these facilities reported 15, 2 and 74% increase in uptake of family planning, antenatal care and facility-based deliveries, respectively. This was statistically significant for family planning pre- (Mean (M) = 1014; Standard deviation (SD) = 381) versus post- (M = 1163; SD = 400); t (18) = − 0.603, P = 0.04) as well as facility-based deliveries pre- (M = 185; SD = 216) versus post- (M = 323; SD = 384); t (18) = − 0.698, P = 0.03). Conclusions A structured, community-participatory intervention enhanced uptake of family planning services and facility-based deliveries in a rural Kenyan setting. This approach is useful in addressing demand-side factors by providing communities with a stake in influencing their health outcomes.